Developmental Changes of Glutamate and GABA Receptor Densities in Wistar Rats - Behuet, Sabrina; Cremer, Jennifer Nadine; Cremer, Markus; Palomero-Gallagher, Nicola; Zilles, Karl; Amunts, Katrin (Frontiers in Neuroanatomy, 2019)
Neurotransmitters and their receptors are key molecules of signal transduction and subject to various changes during pre- and postnatal development. Previous studies addressed ontogeny at the level of neurotransmitters and expression of neurotransmitter receptor subunits. However, developmental changes in receptor densities to this day are not well understood. Here, we analyzed developmental changes in excitatory glutamate and inhibitory γ-aminobutyric acid (GABA) receptors in adjacent sections of the rat brain by means of quantitative in vitro receptor autoradiography. Receptor densities of the ionotropic glutamatergic receptors α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA), kainate and N-methyl-D-aspartate (NMDA) as well as of the ionotropic GABAA and metabotropic GABAB receptors were investigated using specific high-affinity ligands. For each receptor binding site, significant density differences were demonstrated in the investigated regions of interest (olfactory bulb, striatum, hippocampus and cerebellum) and developmental stages (postnatal day (P) 0, 10, 20, 30 and 90). In particular, we showed that the glutamatergic and GABAergic receptor densities were already present between P0 and P10 in all regions of interest, which may indicate the early relevance of these receptors for brain development. A transient increase of glutamatergic receptor densities in the hippocampus was found, indicating their possible involvement in synaptic plasticity. We demonstrated a decline of NMDA receptor densities in the striatum and hippocampus from P30 to P90, which could be due to synapse elimination, a process that redefines neuronal networks in postnatal brains. Furthermore, the highest increase in GABAA receptor densities from P10 to P20 coincides with the developmental shift from excitatory to inhibitory GABA transmission. Moreover, the increase from P10 to P20 in GABAA receptor densities in the cerebellum corresponds to a point in time when functional GABAergic synapses are formed. Taken together, the present data reveal differential changes in glutamate and GABA receptor densities during postnatal rat brain development, which may contribute to their specific functions during ontogenesis, thus providing a deeper understanding of brain ontogenesis and receptor function.